2011
DOI: 10.1158/1078-0432.ccr-10-2504
|View full text |Cite
|
Sign up to set email alerts
|

Targeting the BMK1 MAP Kinase Pathway in Cancer Therapy

Abstract: The big mitogen activated protein kinase 1 (BMK1) pathway is the most recently discovered and leaststudied mammalian mitogen-activated protein (MAP) kinase cascade, ubiquitously expressed in all types of cancer cells tested so far. Mitogens and oncogenic signals strongly activate this cellular MAP kinase pathway, thereby passing down proliferative, survival, chemoresistance, invasive, and angiogenic signals in tumor cells. Recently, several pharmacologic small molecule inhibitors of this pathway have been deve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
34
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(34 citation statements)
references
References 64 publications
0
34
0
Order By: Relevance
“…Activated by growth factors, ERK1/2 and BMK1 pathways promote cell proliferation and survival. While JNK and p38 pathways regulate cell death and proliferation1112. Among the MAPKs, BMK1 is the most similar to ERK1/2.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Activated by growth factors, ERK1/2 and BMK1 pathways promote cell proliferation and survival. While JNK and p38 pathways regulate cell death and proliferation1112. Among the MAPKs, BMK1 is the most similar to ERK1/2.…”
mentioning
confidence: 99%
“…Among the MAPKs, BMK1 is the most similar to ERK1/2. Hence, it is not surprising that BMK1 share a bunch of substrates with ERK1/21112. In response to extracellular signals, BMK1 is specifically activated by MEK5 (mitogen-activated protein kinase kinase 5) and translocates to the cell nucleus and regulates gene expression by phosphorylating1213.…”
mentioning
confidence: 99%
“…Although the full extent of MEK5/ERK5 signaling contribution to cancer remains incompletely understood, a central role in sustaining proliferation is currently recognized [13, 14]. Indeed, previous studies showed that activated ERK5 may support proliferation by promoting G1-S [33] and G2-M phase transitions [34].…”
Section: Discussionmentioning
confidence: 99%
“…Of particular interest, the extracellular signal-regulated kinase 5 (ERK5 or BMK1), together with its upstream activator MAPK kinase 5 (MEK5), mediate the most recently described MAPK pathway [10]. Importantly, aberrant MEK5/ERK5 signaling has been reported in several types of human cancer, including colon cancer [11, 12], and its association with increased cell proliferation, tumor angiogenesis and metastasis is becoming increasingly recognized [13, 14]. Notably, we have recently demonstrated that MEK5 and ERK5 expression is increased in human colon adenomas and adenocarcinomas, and that ERK5 overexpression correlates with increased invasion, as well as with presence of lymph node and distant metastasis [11].…”
Section: Introductionmentioning
confidence: 99%
“…The former pathway is particularly relevant because synthetic ERK inhibitors are being used in clinical trials in a number of cancers (41) and because an ERK5-specific inhibitor has recently been developed (42). Previously published research demonstrated that Van was an antitumor agent that blocks two pathways, EGFR and VEGFR-2 signaling (32).…”
Section: Erk5 and Creb Silencing Enhance MM Cell Toxicitymentioning
confidence: 99%